Warm-ups for youth athletes: making the first 15-minutes count - Myburgh, G. K.; Pfeifer, C. E.; Hecht, C. J. (Strength and Conditioning Journal, 2020)
Warm-up procedures have been found to have a significant influence on fitness performance in youth athletes. As such, warming up before exercise and competition is encouraged and is a widely accepted practice with children and adolescents. Differences in structure, type, duration, intensity, and content of warm-up protocols have led to considerable variation in warm-up procedures. As a result, there is a lack of consensus on the ideal method for preparing youth athletes for exercise and sport. This article, therefore, aims to review current warm-up classifications and considerations of youth athletes, while providing a template of appropriate exercises that can be used safely and effectively in individuals of varying capabilities.